Integrasi Nilai-Nilai Antikorupsi dalam Materi Pendidikan Agama Islam - M. Mualif (Faculty of Islamic Studies, University of Muhammadiyah Jakarta, 2022)
This research study is how the integration of anti-corruption values in PAI subjects in schools can shape students' morals and ethics in developing an anti-corruption movement explicitly and implicitly. However, anti-corruption values will never be achieved without the awareness of the teacher in applying them in the learning process both inside and outside the classroom. This study uses a type of library research with content analysis methods through the data sources of PAI textbooks (Qur'an Hadith, Akidah Akhlak, Fikih and history of Islam). The results show that the integration of anti-corruption values into Islamic religious education materials can be done both textually and contextually by developing character values from the material taught in high school in the preparation of syllabus and lesson plans (RPP). The new textual Islamic religious education material limits the cultivation of honesty, discipline, hard work, care and justice without directly anti-corruption in instilling students' understanding and character. Then contextually it can be done with various kinds of efforts, such as the example of all teachers (especially Islamic religious education teachers), as well as various cultures as a comprehensive anti-corruption value planting with habituation (habits) in schools.